Cartografias territoriais: infância e adolescência nas práticas intersetoriais entre a saúde e a assistência social - Alcântara, Luiza Maria Escardovelli (2019)
The intersectoriality, understood as an articulation between subjects of different social sectors, and therefore, of different knowledge, is shown as a fundamental strategy of work within the public policies of health and social assistance to obtain an intervention able to guarantee service to various users’ demands and also to face complex problems. This way, the objective of this study was to characterize and analyze the intersectoral practices between a child mental health service and a social welfare service located in the central region of the city of São Paulo, in the care and interest of homeless children and adolescents. Therefore, through document analysis and literature review, we initially characterize the scope of action of health and assistance policies, in the interface with childhood and adolescence, with a focus on intersectoriality. We have contextualized in this work the living conditions of homeless children and how this policies apply to them, a group that is the most systematic target of intersectoral actions. In order to accompany the teams in their intersectoral practices with children and adolescents, during the course of a year, the methods of cartographic and field journaling were used. The material was analyzed based on four parameters, three from the legal frameworks of the policies themselves: social protection, integral care, co-responsibility and one of analytical nature, the transversality, which presume the production of the common among heterogeneous, from the perspective of analysis institution. It was found that even if the social assistance policy is a public policy that manages articulations, it is still incipient in the practice of intersectoral work. In addition, it was clear that the tensions between the health and social care fields related to the care of homeless children and adolescents and the need to construct a common view that ensures their rights according the Child and Adolescent Statute